2018
DOI: 10.1080/03007995.2018.1502659
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and network meta-analysis of clinical outcomes associated with isavuconazole versus relevant comparators for patients with invasive aspergillosis

Abstract: This data suggests that the efficacy of isavuconazole for treatment of IA is superior to AmB-D and comparable with both L-AmB and voriconazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
14
0
2
Order By: Relevance
“…Higher survival rates were identified at 12 weeks for possible versus probable/proven cases in the 3 mg/kg group (82% vs 58%; P = 0.06) compared with the 10 mg/kg group (65% vs 50%; P = 0.15) 172 . Notably, while response rates to voriconazole and liposomal amphotericin are comparable across these trials in meta‐analysis, no head to head comparison has been undertaken 148 . Based on voriconazole's more favourable toxicity profile and ease of administration as compared to liposomal amphotericin B and the above data, liposomal amphotericin is recommended with moderate support as an alternative treatment regimen in patients who develop IA while receiving a mould‐active azole or those intolerant to voriconazole ( Moderate recommendation, Level II evidence ; Table 5).…”
Section: Question 9: What Recommendations Should Guide the First‐line Antifungal Treatment Of Ia In Haematology/oncology Patients?mentioning
confidence: 99%
“…Higher survival rates were identified at 12 weeks for possible versus probable/proven cases in the 3 mg/kg group (82% vs 58%; P = 0.06) compared with the 10 mg/kg group (65% vs 50%; P = 0.15) 172 . Notably, while response rates to voriconazole and liposomal amphotericin are comparable across these trials in meta‐analysis, no head to head comparison has been undertaken 148 . Based on voriconazole's more favourable toxicity profile and ease of administration as compared to liposomal amphotericin B and the above data, liposomal amphotericin is recommended with moderate support as an alternative treatment regimen in patients who develop IA while receiving a mould‐active azole or those intolerant to voriconazole ( Moderate recommendation, Level II evidence ; Table 5).…”
Section: Question 9: What Recommendations Should Guide the First‐line Antifungal Treatment Of Ia In Haematology/oncology Patients?mentioning
confidence: 99%
“…A systematic review on clinical outcomes associated with isavuconazole versus comparators for patients with IA suggested that isavuconazole is superior to AmB deoxycholate and comparable to both liposomal AmB and voriconazole. 231 As distinction between aspergillosis and mucormycosis is not always easy at early stage of the disease, the activity of isavuconazole against Mucorales is an additional advantage for the use as preemptive therapy of a suspected mold infection. 232 Guidelines suggested that therapeutic drug monitoring of isavuconazole could be useful in case of nonresponse to treatment, unexpected toxicity, potential drug-to-drug interactions, treatment of pathogens with elevated MICs or treatment of central nervous system infections.…”
Section: Eortc/msg Criteria For Severely Immunosuppressed Patientsmentioning
confidence: 99%
“…No pharmacokinetic studies have so far formally addressed whether the use of a moderate rather than a strong CYP3A4 inhibitor, like isavuconazole, may allow a lower reduction of ibrutinib dosage. An alternative treatment for filamentous fungi invasive disease could be based on the use of either liposomal amphotericin B, which has no effects on ibrutinib metabolism [155].…”
Section: Discussionmentioning
confidence: 99%